Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Agenda. Last April was an important milestone for the institution. The commitment to increase Fund resources by over USD 430 billion on a temporary basis attests to the membership's willingness to act collectively and decisively to get ahead of the crisis. For our part, we must continue to support these efforts with clear and pointed advice on macro financial policies, and strong and well-designed programs. This is true not only for Europe, where the risks to stability have been acute, but across the span of the membership. We need to continue to offer pragmatic remedies to the main risks confronting the global economy, help members address spillovers, and support their economic transitions and development agendas. We need also to strengthen our internal processes, with reforms of surveillance, quotas and governance. These points, which draw on my Action Plan of last month and feedback from members during the Spring Meetings, are elaborated in the work plan below.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet